2007
DOI: 10.1007/s11664-007-0289-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ta-based Diffusion Barriers on the Microstructure of Copper Thin Films

Abstract: Copper represents the most commonly used interconnect material in ultra large-scale integration (ULSI) technology. Given that the successful implementation of Cu requires the use of underlying diffusion barriers, these studies were focused on the influence of Ta-based barrier layers on the microstructure of physical vapor deposited (PVD) and electrochemically deposited (ECD) Cu thin films. The variation of a-Ta, b-Ta, TaSiN, and TaN as an underlayer caused a modification of the PVD Cu seed-layer texture, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…Since the variability in the values listed in Table 1 cannot be ascribed to the plating parameters, other possible causes were investigated. In a previous study where full wafers were used, In the past literature several groups, including Ueno and co-workers, ascribed such differences to variability in thickness [7][8][9][10]12]. In our work, no variation of plating power across the small plating area is expected, and profilometry measurements and FIB cross sections coupled with SEM analysis confirmed that uniform thickness was achieved for all coupons.…”
Section: Iv-2 Effect Of Cu Seed Layer Texturesupporting
confidence: 69%
See 2 more Smart Citations
“…Since the variability in the values listed in Table 1 cannot be ascribed to the plating parameters, other possible causes were investigated. In a previous study where full wafers were used, In the past literature several groups, including Ueno and co-workers, ascribed such differences to variability in thickness [7][8][9][10]12]. In our work, no variation of plating power across the small plating area is expected, and profilometry measurements and FIB cross sections coupled with SEM analysis confirmed that uniform thickness was achieved for all coupons.…”
Section: Iv-2 Effect Of Cu Seed Layer Texturesupporting
confidence: 69%
“…2 is approached through imposing tight controls on plating current, time, and chemistry [2][3][4][5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When The resistivity decrease and α value change with the keeping time showed similar trends, and this suggests that grain growth was controlled by the film texture. While slight amount of {511} grains were reported to exist in addition to {111} and {100} grains in EBSD observation of Cu films [27][28][29][30], unfortunately the (511) Cu peak is out of range of 2θ in the θ-2θ scan using the Cu K α -ray, and thus the (511) texture was evaluated by θ scan, as mentioned before. Typical XRD spectra of the θ scan (2θ = 50.5°) for ten samples after keeping at RT for about 200 or more days are shown in Figure 4.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the mechanical and electrical properties of the metallization need to be tailored to match the requirements of the assembly technology. If an electro-chemical deposition (ECD) of Cu is implemented in the process chain, the microstructure of the commonly sputtered seed-layer is partly passed on to the ECD layer [4].…”
Section: Introductionmentioning
confidence: 99%